Habitat-specific shaping of proliferation and neuronal differentiation in adult hippocampal neurogenesis of wild rodents - Cavegn, Nicole; van Dijk, R. Maarten; Menges, Dominik; Brettschneider, Helene; Phalanndwa, Mashudu; Chimimba, Christian T.; Isler, Karin; Lipp, Hans-Peter; Slomianka, Lutz; Amrein, Irmgard (Frontiers in Neuroscience, 2013)
Daily life of wild mammals is characterized by a multitude of attractive and aversive stimuli. The hippocampus processes complex polymodal information associated with such stimuli and mediates adequate behavioral responses. How newly generated hippocampal neurons in wild animals contribute to hippocampal function is still a subject of debate. Here, we test the relationship between adult hippocampal neurogenesis and habitat types. To this end, we compare wild Muridae species of southern Africa (Namaqua rock mouse (Micaelamys namaquensis), red veld rat (Aethomys chrysophilus), highveld gerbil (Tatera brantsii) and spiny mouse (Acomys spinosissimus)) with data from wild European Muridae (long-tailed wood mice (Apodemus sylvaticus), pygmy field mice (Apodemus microps), yellow-necked wood mice (Apodemus flavicollis), and house mice (Mus musculus domesticus)) from previous studies. The pattern of neurogenesis, expressed in normalized numbers of Ki67- and DCX-positive cells to total granule cells, is similar for the species from a southern African habitat. However, we found low proliferation, but high neuronal differentiation in rodents from the southern African habitat compared to rodents from the European environment. Within the African rodents, we observe additional regulatory and morphological traits in the hippocampus. Namaqua rock mice with previous pregnancies showed lower adult hippocampal neurogenesis compared to males and nulliparous females. The phylogenetically closely related species (Namaqua rock mouse and red veld rat) show a CA4, which is not usually observed in murine rodents. The specific features of the southern environment that may be associated with the high number of young neurons in African rodents still remain to be elucidated. This study provides the first evidence that a habitat can shape adult neurogenesis in rodents across phylogenetic groups.